Competition in Services and Efficiency of Manufacturing Firms:Does Liberalization Matter? - Emanuele Forlani (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2012)
In developed economies, services firm an increasing proportion of inputs employed by manufacturing firms. While downstream firms act in a very competitive environment, services often operate in protected or highly regulated markets. In this paper, I empirically investigate whether the degree of competition in services affects the efficiency of manufacturing firms through services production inputs. By using both firm and sector level data for France, through input-output analysis I show that variations in the upstream competition, especially in network industries, affect the average productivity level in manufacturing industry: an increase in average markups is associated with a reduction in manufacturing productivity. The findings differ according to firms size and initial efficiency level: in the short run less efficient and small firms are relatively mostly hfirmed by an uncompetitive service sector.
Keywords: D24; L11; L51; L80; 330; Service sector; competition; productivity; I-O tables